Food Factors for Health Promotion - Yoshikawa, Toshikazu (Forum of nutrition, 2009)
Genomics for food functionality and safety / Abe, K. -- Lipid metabolism and nutrigenomics : impact of sesame lignans on gene expression profiles and fatty acid oxidation in rat liver / Ide, T. ... [et al.] -- Genome science of lipid metabolism and obesity / Takahashi, N. ... [et al.] -- Oxidative stress-induced posttranslational modification of proteins as a target of functional food / Naito, Y., Yoshikawa, T. -- Absorption and function of dietary carotenoids / Nagao, A. -- Metabolism of flavonoids / Wang, Y., Ho, C.-T. -- [beta]-carotene degradation products : formation, toxicity, and prevention of toxicity / Siems, W. ... [et al.] -- Dietary flavonoids as antioxidants / Terao, J. -- Inflammatory components of adipose tissue as target for treatment of metabolic syndrome / Yu, R., Kim, C.-S., Kang, J.-H. -- Soybean isoflavones in bone health / Ishimi, Y. -- Probiotics in primary prevention of atopic dermatitis / Ji, G.E. -- Astaxanthin protects neuronal cells against oxidative damage and is a potent candidate for brain food / Liu, X., Osawa, T. -- Function of marine carotenoids / Miyashita, K. -- Exercise and food factors / Aoi, W. -- Molecular basis for cancer chemoprevention by green tea polyphenol EGCG / Tachibana, H. -- Chemoprevention by isothiocyanates : molecular basis of apoptosis induction / Nakamura, Y. -- Ginger-derived phenolic substances with cancer preventive and therapeutic potential / Kundu, J.K., Na, H.-K., Surh, Y.-J. -- Chemoprevention with phytochemicals targeting inducible nitric oxide synthase / Murakami, A. -- Chemoprevention of tocotrienols : the mechanism of antiproliferative effect / Wada, S
Keywords: Konferenzschrift -- 2007 -- Kioto; Functional Food; Ernährung